Edge of awareness 25 contemporary essays - Hoopes, Ned E.; Peck, Richard 1934- (New York, N.Y. Dell Publishing Co., Inc., 1966)
Contains essays in five catagories: Defining oneself and others; Searching for meaning in a complex society; Attaining a unique place; Responding to creative experiences; Surviving through science.
Defining Oneself and Others. On running away / John Keats -- Alone on a mountain top / Jack Kerouac -- Old man facing death / Oliver La Farge -- Portrait of Hemingway-preface, 1961 / Lillian Ross -- Real women / Robert Graves -- Searching for Meaning in a Complex Society. What I believe / E.M. Forster -- Can we survive the fun explosion? / Joseph Wood Krutch -- Why I dislike western civilization / Arnold Toynbee -- Fire walking in Ceylon / Leonard Feinberg -- One vote for this age of anxiety / Margaret Mead -- Attaining a Unique Place. Eleanor Roosevelt: the awakening / Archibald MacLeish -- Her journeys are over / Adlai E. Stevenson -- The Harvard man who put the ease in Casey's manner / Martin Gardner -- The monster / Deems Taylor -- My Uncle Koppel and free enterprise / Harry Golden -- Responding to Creative Experiences. Salt crystals, spider webs, and words / Paul Engle -- Robert Frost: the way to the poem / John Ciardi -- So long as the theater can do miracles / Tyrone Guthrie -- TV shows are not supposed to be good / David Karp -- The fine edge of awareness / Russell Lynes -- How do you know it's good? / Marya Mannes -- Surviving Through Science. Can science prevent war? / Arthur Larson -- We'll never conquer space / Arthur C. Clarke -- Portrait of Homo aquaticus / James Dugan -- "Science, life and landscape" / Paul B. Sears.
Keywords: American essays -- 20th century; English essays -- 20th century